Avaliação de suscetibilidade à erosão e movimentação gravitacional de massa no Parque Estadual do Juquery, Franco da Rocha (SP) - De Araújo Amorim, Danilo Gonçalves [UNESP]; Zaine, José Eduardo [UNESP]; Bocarde, Danielle; Rodrigues, Flávio Henrique [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
The area of this study is the State Park of Juquery, located in the city of Franco da Rocha, Metropolitan Region of São Paulo, Brazil, characterized by a protected area of a remnant cerrado. This protected area has registered problems caused by flooding processes, mass movements and hydric erosion. Based on this framework, this study aims to evaluate the susceptibility to linear erosion and soil and rock slides, and support the planning and management of the physical environment of the that conservation unit. The mapping performed in the scale of 1:20.000 subdivided the area of study in six geological-geotechnical unit, whose results have fostered the evaluation of susceptibility to geological processes concerned. The susceptibility assessment analyzed the possibility of morpho-dynamic processes in relation to the geological and geotechnical characteristics and was carried out in a qualitative manner with application of graphical analysis method, which is based on the combinatory analysis of variables of interest. To this end, geoprocessing techniques, field surveys and graphical analysis were used. As a result, maps of susceptibility to erosion and landslide processes are presented. The erosion map shows that 95% of the park area has moderate susceptibility to the processes and 5% is considered high susceptibility. Concerning landslides, 88% has low sensitivity and 12% is considered moderate susceptibility. Two points of interest were identified, a gully at the west end, and a road with widespread ravines. It is concluded that linear erosion are the main geological-geotechnical problems of the State Park of Juquery, arising from natural characteristics of the physical environment and aggravated by the absence of vegetation cover and precariousness of roads and trails within the conservation unit.
Assessment of suscetibility to erosion and mass movements in the Statepark of Juquery, Franco da Rocha, São Paulo State, Brazil
Keywords: Assessment of Susceptibility; Engineering geology; Environmental Management; Geotechnical Cartography; Gravitational Mass Movements; Linear Erosion